Nanostructured Black Nickel Coating as Replacement for Black Cr(VI) Finish - Marina M. Mennucci; Rodrigo Montes; Alexandre C. Bastos; Alcino Monteiro; Pedro Oliveira; João Tedim; Mário G. S. Ferreira (Applied Sciences, 2021)
This work compares different electrodeposition procedures to produce nickel black coatings as greener and less toxic alternatives to Cr(VI)-based coatings used in different applications. Nickel and nickel-plated brass served as substrates in studies with a Hull cell and polarization curves. After a set of comparative experiments, the best electrodeposition procedure was further studied and optimized. Optimal conditions were found with a bath consisting of 75 g/L NiCl2·6H2O + 30 g/L NaCl and a current density of 0.143 A dm−2 applied for 5 min at room temperature. Furthermore, a pre-treatment with 18.5 vol.% of hydrochloric acid in water was found to be necessary to warrant good coating adhesion to the substrate. The black color is attributed to the development of a nanostructured surface that absorbs the incident light. Corrosion testing was performed in 0.5 M NaCl aqueous solution using electrochemical impedance spectroscopy (EIS) and polarization tests.